2017
DOI: 10.1007/s11695-017-2666-x
|View full text |Cite|
|
Sign up to set email alerts
|

Bariatric Surgery and Endoluminal Procedures: IFSO Worldwide Survey 2014

Abstract: Background and aimSeveral bariatric surgery worldwide surveys have been previously published to illustrate the evolution of bariatric surgery in the last decades. The aim of this survey is to report an updated overview of all bariatric procedures performed in 2014.For the first time, a special section on endoluminal techniques was added.MethodsThe 2014 International Federation for the Surgery of Obesity and Metabolic Disorders (IFSO) survey form evaluating the number and the type of surgical and endoluminal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
358
0
30

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(389 citation statements)
references
References 16 publications
1
358
0
30
Order By: Relevance
“…Furthermore, severe/morbid obese individuals represent the only eligible candidates for bariatric surgery (BS), a treatment which has dramatically increased worldwide7 as it reduces cardiovascular risks and improves metabolic conditions 8. BS represents a good model to understand the intestinal contribution to health improvements by comparing adjustable gastric banding (AGB), a procedure solely inducing caloric restriction due to gastric volume reduction (equivalent to a successful diet intervention), and Roux-en-Y-Gastric bypass (RYGB), which by contrast drastically rearranges the digestive tract architecture and adds intestinal malabsorption to food intake reduction 9.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, severe/morbid obese individuals represent the only eligible candidates for bariatric surgery (BS), a treatment which has dramatically increased worldwide7 as it reduces cardiovascular risks and improves metabolic conditions 8. BS represents a good model to understand the intestinal contribution to health improvements by comparing adjustable gastric banding (AGB), a procedure solely inducing caloric restriction due to gastric volume reduction (equivalent to a successful diet intervention), and Roux-en-Y-Gastric bypass (RYGB), which by contrast drastically rearranges the digestive tract architecture and adds intestinal malabsorption to food intake reduction 9.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only effective treatment for obesity and sustained weight loss is surgery, with the two most common bariatric operations used as a treatment for obesity and associated metabolic disorder being the vertical sleeve gastrectomy (VSG) and the Roux-en-Y gastric bypass (RYGB) surgery. A recent worldwide survey (Angrisani, Santonicola et al 2017) found the most commonly performed procedure in the world was VSG that reached 45.9%, followed by Roux-en-Y gastric bypass (RYGB) (39.6%). The older RYGB procedure involves creating a stomach pouch out of a small portion of the stomach and attaching it directly to the small intestine, bypassing a large part of the stomach and the entire duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-surgical options, bariatric surgery results in greater improvement in weight loss and weight-associated comorbidities 2. Laparoscopic Roux-en-Y gastric bypass (RYGB) is the second most commonly performed bariatric procedure in the world 3. It greatly reduces the stomach size by approximately 95%, creating a small pouch.…”
Section: Introductionmentioning
confidence: 99%